2017
DOI: 10.1037/ccp0000241
|View full text |Cite
|
Sign up to set email alerts
|

Applying network analysis to psychological comorbidity and health behavior: Depression, PTSD, and sexual risk in sexual minority men with trauma histories.

Abstract: Objective High rates of depression and PTSD contribute to sexual risk, particularly in men who have sex with men (MSM) who have experienced childhood sexual abuse. The comorbidity between depression and PTSD and mechanisms by which they contribute to sexual risk in MSM remain unclear. This study sought to demonstrate the feasibility and utility of a novel network approach to (1) characterize symptom interconnections between depression and PTSD in MSM, (2) identify specific symptoms related to sexual risk behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 86 publications
(116 reference statements)
6
56
0
1
Order By: Relevance
“…Two studies analyzed depression and PTSD [70, 71] and found that symptoms of depression and PTSD formed separated clusters but they were also connected by bridge symptoms, such as “sleep disruption” or “concentration difficulties” (online suppl. Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies analyzed depression and PTSD [70, 71] and found that symptoms of depression and PTSD formed separated clusters but they were also connected by bridge symptoms, such as “sleep disruption” or “concentration difficulties” (online suppl. Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…To date, no network analytic study of which we are aware has examined the relations between a variety of reckless behaviors and specific PTSD symptoms and/or symptom clusters. One study examined the association between PTSD and one form of reckless behaviors—risky sexual behavior (Choi, Batchelder, Ehlinger, Safren, & O'Cleirigh, 2017). In a United States–based sample of 296 men who have sex with other men, the authors found that the strongest connection between PTSD, as diagnosed using criteria from the fourth edition of the DSM ( DSM‐IV ), and risky sexual behavior was through PTSD Symptom C1: avoidance of memories, thoughts, and feelings related to the traumatic event.…”
Section: Symptom Clusters In the Dsm‐5 Seven‐factor Hybrid Model (Armmentioning
confidence: 99%
“…In a United States-based sample of 296 men who have sex with other men, the authors found that the strongest connection between PTSD, as diagnosed using criteria from the fourth edition of the DSM (DSM-IV), and risky sexual behavior was through PTSD Symptom C1: avoidance of memories, thoughts, and feelings related to the traumatic event. The authors concluded that these results underscored the importance of including skills that increase mindfulness and tolerance of distressing memories in interventions for PTSD (Choi et al, 2017).…”
mentioning
confidence: 96%
“…In a recent paper, researchers showed that these PTSD network structures replicated well across four different samples of traumatized patients receiving treatment (Fried et al., ). Studies have also investigated the comorbidity of PTSD with other diagnostic constructs, such as depression and substance abuse (Afzali et al., 2016; Choi, Batchelder, Ehlinger, Safren, & O'Cleirigh, ). However, to our knowledge, no network study has modeled PTSD symptoms together with specific individual negative emotions.…”
mentioning
confidence: 99%